2020
DOI: 10.3390/polym12040886
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Types of Peroxides on the Long-Chain Branching of PP via Reactive Extrusion

Abstract: Long-chain branching (LCB) is known as a suitable method to increase the melt strength behavior of linear polypropylene (PP), which is a fundamental weakness of this material. This enables the modification of various properties of PP, which can then be used—in the case of PP recyclates—as a practical “upcycling” method. In this study, the effect of five different peroxides and their effectiveness in building LCB as well as the obtained mechanical properties were studied. A single screw extruder at different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…For 90:10 blends, the curve of PODIC is located above all other curves while for higher PS concentration it is located below LUC and SIS and in the low frequency range even below the uncompatibilized blend. In recently published work from our research group, similar behavior was observed for the reactive extrusion of PP at 240 C indicating the generation of a highly branched structure which was also confirmed by extensional rheology measurements [ 52 ]. A decrease in complex viscosity, as observed for 75:25 blends, is usually related to dominant chain scission during reactive extrusion with peroxides [ 25 ].…”
Section: Results and Discussionsupporting
confidence: 77%
“…For 90:10 blends, the curve of PODIC is located above all other curves while for higher PS concentration it is located below LUC and SIS and in the low frequency range even below the uncompatibilized blend. In recently published work from our research group, similar behavior was observed for the reactive extrusion of PP at 240 C indicating the generation of a highly branched structure which was also confirmed by extensional rheology measurements [ 52 ]. A decrease in complex viscosity, as observed for 75:25 blends, is usually related to dominant chain scission during reactive extrusion with peroxides [ 25 ].…”
Section: Results and Discussionsupporting
confidence: 77%
“…[100] Here, the possibility of crosslinking also cannot be ruled out. [101] Chain scission is more prominent than recombination in the melt, whereas the reverse happens below the melting point. Hence, a stabilizing reagent is required during the extrusion process.…”
Section: Polypropylenementioning
confidence: 99%
“…Nevertheless, it has been shown that these properties can be improved by introducing long-chain branching (LCB) to linear polyolefins [2][3][4]. Different methodologies have been developed, such as the ethylene copolymerization with vinylterminated polyolefins (macromonomers) [5,6], copolymerization with a non-conjugated α,ωdiene [7][8][9][10][11], as well as processes involving radical mechanisms [12][13][14][15][16][17][18]. Nevertheless, the materials produced with these methodologies generally exhibit complex molecular structures and/or uneven branch distribution.…”
Section: Introductionmentioning
confidence: 99%